Impact of Education on Fluoroquinolone Use in Uncomplicated Cystitis. (4th October 2017) - Ferren, Ryan; Lee, Helen; Park, Steven; Thrupp, Lauri; Hsieh, Lanny
Abstract: Background: The Food and Drug Administration released a safety alert in May 2016 against the use of fluoroquinolones (FQ) in uncomplicated infections including uncomplicated cystitis due to concern for increased risk of disabling and potentially permanent adverse drug effects (ADEs). The aim of the study is to compare the rates of FQ prescriptions for uncomplicated cystitis before and after prescriber education to assess if prescriber education decreases the use of FQs. Methods: This is a single-center, two-phase retrospective chart review comparing a five year pre-intervention and a four month post-intervention periods that evaluated patients seen at UC Irvine's emergency department (ED) or outpatient clinics for uncomplicated cystitis. Adult female, non-pregnant patients 18 years of age or older with the diagnosis of uncomplicated cystitis were included. The treatment guideline for uncomplicated cystitis was developed by the antibiotic stewardship subcommittee with the recommendation to use nitrofurantoin as the first line agent. The infectious diseases pharmacy resident provided educational sessions from December 2016 to January 2017. The primary objective is to evaluate the impact of prescriber education on FQ prescribing rates for uncomplicated cystitis in the ED and outpatient clinics. Secondary objectives include the resistance rates of FQ and trimethoprim/sulfamethoxazole (TMP/SMX) against uropathogens to determine the local resistance rates and ADEs due to FQs. Results: A total of 1056 patients were included in the analysis: 974 in the pre-intervention and 82 in the post-intervention groups. The rate of FQ prescriptions decreased from 32.3% in the pre-intervention group to 13.1% in the post-intervention group ( P = 0.0002). The overall resistance rates of uropathogens were 19.3% to FQ and to 34.3% to TMP/SMX. There were 5 (0.5%) ADEs in the pre-intervention and 2 (2.5%) in the post-intervention groups. Conclusion: Prescriber education regarding the appropriate treatment of uncomplicated cystitis and proper use of FQs was effective in reducing the rate of FQ prescriptions in management of uncomplicated cystitis. After prescriber education, the rate of FQ prescriptions decreased by 59%. Disclosures: All authors: No reported disclosures.